2014
DOI: 10.1111/pin.12207
|View full text |Cite
|
Sign up to set email alerts
|

Two autopsy cases of severe fever with thrombocytopenia syndrome (SFTS) in Japan: A pathognomonic histological feature and unique complication of SFTS

Abstract: We report two autopsy cases of severe fever with thrombocytopenia syndrome (SFTS) with a high fatality rate in aged Japanese patients. Both cases were caused by a tick-bite. The pathognomonic histological feature was necrotizing lymphadenitis of systemic lymphoid tissue with SFTS viruses and SFTSV-RNA copies. Marked fungal infections were also observed in the lungs of both patients. Since cellular immune function may be suppressed in SFTS patients, physicians should be aware of possible fungal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
92
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 16 publications
11
92
0
1
Order By: Relevance
“…Two of the patients with SFTS who died underwent autopsies and the pathological findings were reported (12). Although the novel findings in the report were fungal infections in the respiratory tract organs, there was no mention of whether the ulcerative lesions were present or not in the patients with SFTS, suggesting that ulcerative lesions were not observed in these patients.…”
mentioning
confidence: 51%
“…Two of the patients with SFTS who died underwent autopsies and the pathological findings were reported (12). Although the novel findings in the report were fungal infections in the respiratory tract organs, there was no mention of whether the ulcerative lesions were present or not in the patients with SFTS, suggesting that ulcerative lesions were not observed in these patients.…”
mentioning
confidence: 51%
“…Virological and pathological examinations in Japanese patients with SFTS revealed that SFTS virus replicates in blastic cells in the local lymph nodes, but not in the major organs [3,12]. However, the kidney was not examined in these studies.…”
Section: Discussionmentioning
confidence: 95%
“…Epidemiological study shows that 1.0%-3.8% of the examined population in hilly areas had SFTSV antibodies, which suggests that SFTSV has circulated widely in China, especially in rural areas [5]. SFTSV infection was also reported in other Asia countries such as Korea and Japan [6,7]. The mortality of SFTSV infection in China is about 2.5%-30% [8].…”
Section: Introductionmentioning
confidence: 93%
“…The disease occurs mainly in April and May during the peaking season in Henan [9]. One study indicated that SFTSV could cause the asymptomatic infections via person-to-person contact with infected blood [6]. At present; there is no specific medication to treat this disease.…”
mentioning
confidence: 99%